Homoconjugalidades femininas : um estudo sobre relacionamentos entre mulheres - Silva, Gabriela Boldrini da (2018)
The objective of the present work is to grasp the marital dynamics of sexual-affective relationships between women. Particularly, the aim is to identify the consequences of the condition of invisibility attributed to relationships between women, as well as describing the diversity of experiences related to familiar, social and personal life in the participants’ journey and to point out lesbophobia-related elements. It is a descriptive study of qualitative approach, in the form of a phenomenological study. The participants were 5 (five) women, ages 25 to 37 years old, that are involved in a sexual-affective relationship with other women, in the form of cohabitation for at least 1 (one) year. The methodology used for the picking of participants was the snowball method. The instrument used for data collection was based on a semi-structured interview script consisting of 36 (thirty-six) questions. For data analysis it was used the phenomenological method for psychological investigation, which revealed 8 (eight) meaning units: relationship characteristics; feelings for the partner; the process of establishment of one’s sexual identity; experiencing of situations of prejudice; support nets and social support; marital conflicts; maternity and perspectives for the future. Data analysis aimed at identifying particularities and converging points in the reported experiences, and were organized in the form of five narratives. Data points towards theses women’s life trajectories being scarred by stigma and violence, the family of origin acting either as a main agent of this violence, either as the main source of support. By contrast, the constituting of a new family is filled by intense affection, companionship and partnership. There are struggles, both internal and external, related to the relationship’s visibility and the constituting of sexual identity, as well as sexuality-management strategies could be observed. Effects of a violence-marked subjectivity could be observed, which become current in the form of internalized lesbophobia and perceptions on gender and sexuality. Understanding the marital dynamics of relationships between women is necessary for the demystification of stigmas that are still perpetuated in the form of violence against lesbians. It is pointed out that for future research it will be desirable to broaden the age range of participants, as well as highlighting pointers of social class and race